The system approach for Sosnowsky’s hogweed control and elamination - Solomiychuk, M.; Gunchak, V.; Kordulyan, R.; Nemchenko, O.M. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2017)
There were proposed the results by the efficient usage of chemical and mechanical measures against Sosnowsky’s hogweed. The complex consists of herbicide usage on the base of glyphosate active matter in the form of acid, 500 g/l, at norm 8 l/ha with preparation dicamba 480 g/l, at norm 0.3 l/ha. The biodestructor is recommended to use too at norm 2 l/ha on cut and dried plants. It allows to elaminate number of plants, prevent seeds maturing and decrease the probability of it’s germinating.